Two Doses of Intravenous Tranexamic Acid Offers No Benefit over One Dose in Total Hip Arthroplasty - Charette, Ryan S.; Bernstein, Jenna A.; Sloan, Matthew; Nchako, Corbyn M.; Kamath, Atul F.; Nelson, Charles L. (The Journal of Hip Surgery, 2020)
Tranexamic acid (TXA) has been shown to reduce blood loss and transfusions in total hip arthroplasty (THA). There is no consensus on the ideal number of doses that best reduces blood loss while limiting complications. Our study compared one versus two doses of intravenous TXA in primary THA and its effect on blood transfusion rate. We retrospectively reviewed patients undergoing primary THA at our two high-volume arthroplasty centers from 2013 to 2016. Patients were included if they underwent unilateral primary THA, and received one or two doses of TXA. Patients receiving therapeutic anticoagulation were excluded. Our primary outcome measure was postoperative transfusion rate. Secondary outcomes included blood loss, length of stay (LOS), rate of deep vein thrombosis/pulmonary embolism (DVT/PE), readmission, and reoperation. A total of 1,273 patients were included; 843 patients received one dose of TXA and 430 patients received two TXA doses. Univariate analysis demonstrated no significant difference in transfusion rate when administering one versus two doses. There was no significant difference in LOS, or rates of DVT/PE, readmission, and reoperation. When comparing patients receiving aspirin prophylaxis, there was a significantly decreased blood volume loss with two doses (1,360 vs. 1,266 mL, mean difference = 94 mL; p = 0.017). In patients, undergoing primary unilateral THA, there is no difference in postoperative transfusion rate with one or two doses of intravenous TXA. There was no difference in thromboembolic events. Given the added cost without clear benefit, these findings support one rather than two doses of TXA during primary THA.
Keywords: total hip arthroplasty; tranexamic acid; blood transfusion